Early development of stricturing or penetrating pattern in Crohn's disease is influenced by disease location, number of flares, and smoking but not by NOD2/CARD15 genotype. Issue 4 (1st April 2003) - Louis, E; Michel, V; Hugot, J P; Reenaers, C; Fontaine, F; Delforge, M; El Yafi, F; Colombel, J F; Belaiche, J
Abstract : Background: Crohn's disease is a heterogeneous entity. Disease behaviour, characterised as stricturing, penetrating, or non-stricturing non-penetrating, is a clinically important phenotype as it is associated with complications and need for surgery. It has recently been showed that the behaviour of Crohn's disease changes over the course of the disease. Aim: To assess the association between rapid development of a penetrating or stricturing pattern of Crohn's disease and demographic and clinical characteristics as well as NOD2/CARD15 genotype. Patients and methods: A total of 163 patients with a firm diagnosis of Crohn's disease and who had non-penetrating non-stricturing disease at diagnosis were studied. Various demographic and clinical characteristics as well as antisaccharomyces cerevisiae antibody status and NOD2/CARD15 genotype were documented in these patients. These characteristics were compared in subgroups of patients according to evolution of disease behaviour five years after diagnosis. Results: Five years after diagnosis there were 110 (67.5%) patients with non- structuring non-penetrating disease, 18 (11%) with stricturing disease, and 35 (21.5%) with penetrating disease. In multivariate analysis, only disease location and number of flares per year were significantly discriminant between the three subgroups (p=0.0009 and 0.0001, respectively). Ileal location of the disease was associated with a stricturing pattern while a high number of flares was associated with a penetrating pattern. Active smoking was also associated with a penetrating pattern compared with a non-stricturing non-penetrating pattern only. Conclusions: Early development of stricturing or penetrating behaviour in Crohn's disease is influenced by disease location, clinical activity of the disease, and smoking habit, but not by NOD2/CARD15 genotype.